Lateral diffusion of surface immunoglobulin, Thy-1 antigen, and a lipid probe in lymphocyte plasma membranes - Dragsten, Paul (1979)
Fluorescence photobleaching recovery was used to measure the lateral diffusion coefficient and mobile fraction of surface immunoglobulin (sIg), Thy-1 antigen, and a lipid probe in the plasma membrane of mouse lymphocytes. The lipid probe (3,3′-dioctadecylindocarbocyanine) had a mean (±SD) diffusion coefficient of (1.7 ± 0.3) × 10(-8) cm(2)/sec, with essentially all of the probe mobile in the membrane. We detected little or no effect on the diffusion of this probe due to the presence of microvilli. Its diffusion was slightly restricted in capped regions. No differences in lipid probe mobility were detected between T and B cells. Fifty to 90% of the detectable sIg and Thy-1 antigen was free to move in the plane of the membrane with diffusion coefficients of ≈3 × 10(-10) cm(2)/sec; the remainder was immobile. Crosslinking of sIg with anti-Ig antibodies (in the presence of azide to inhibit capping) completely immobilized sIg at high concentrations but failed to do so at low concentrations. Thy-1 antigen could not be immobilized with an IgG rabbit anti-mouse brain reagent without an additional layer of crosslinking antibody. In parallel labelings (in the absence of azide), capping of sIg and Thy-1 antigen was observed only under crosslinking conditions sufficient to immobilize the membrane antigen. Sodium azide, colchicine, and cytochalasin B had no measurable effect on lipid probe, sIg, or Thy-1 diffusion.